2023
DOI: 10.1021/acs.est.3c00742
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Pharmaceuticals to DBP Formation and Developmental Toxicity in Chlorination of NOM-containing Source Water

Abstract: Pharmaceuticals have been considered a priority group of emerging micropollutants in source waters in recent years, while their role in the formation and toxicity of disinfection byproducts (DBPs) during chlorine disinfection remains largely unclear. In this study, the contributions of natural organic matter (NOM) and pharmaceuticals (a mixture of ten representative pharmaceuticals) to the overall DBP formation and toxicity during drinking water chlorination were investigated. By innovatively “normalizing” chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…A study by Li et al investigated DBPs (though the measurement of total organic halogen) and the accompanying developmental toxicity following the chlorination of 10 pharmaceuticals . Results showed that a chlorine contact time of 1 h along with 2 mg/L NOM and 0.0062–0.31 mg/L C of pharmaceuticals contributed 80–99.5% and 0.5–20% of total organic halogen, respectively.…”
Section: Drinking Water and Swimming Pool Disinfection Byproductsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Li et al investigated DBPs (though the measurement of total organic halogen) and the accompanying developmental toxicity following the chlorination of 10 pharmaceuticals . Results showed that a chlorine contact time of 1 h along with 2 mg/L NOM and 0.0062–0.31 mg/L C of pharmaceuticals contributed 80–99.5% and 0.5–20% of total organic halogen, respectively.…”
Section: Drinking Water and Swimming Pool Disinfection Byproductsmentioning
confidence: 99%
“…Li et al explored the contribution of pharmaceuticals to the formation of DBPs during chlorination using experimental and modeling approaches . By “normalizing” chlorine exposure and using a kinetic model, the study quantified the contributions of NOM and pharmaceuticals to total organic halogen formation in waters with varying concentrations of pharmaceuticals.…”
Section: Pharmaceuticals and Hormonesmentioning
confidence: 99%
“…The acute toxicity of halobenzoquinone was up to 200 times more potent than haloacetic acids when using zebrafish embryos as a developmental toxicity model, emphasizing the importance of understanding aromatic DBP formation. The formation of aromatic DBPs was investigated in drinking water distribution systems (DWDSs) via chlor(am)inating authentic drinking water under well-controlled laboratory conditions. , However, these studies are not effective in elucidating the variation in the occurrence and abundance of aromatic DBPs in real DWDSs. This is primarily because the contributions of multiple factors influencing DBP formation remain unknown, such as long transportation distances, prolonged reaction time, and unsuspected precursors.…”
Section: Introductionmentioning
confidence: 99%